English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Rewrite the equation y = –2x + 3 as a function of x.

2007-04-28 16:45:36 · 5 answers · asked by Miss Mama 1 in Science & Mathematics Mathematics

5 answers

You need to isolate x.

Add 2x to each side
2x+y = 3

Subtract y from each side
2x = 3 - y

Divide all terms by 2
x = 3/2 - y/2

2007-04-28 16:49:47 · answer #1 · answered by TaxGurl 6 · 0 0

improve the brackets. 3y - 2x - 2 = y + 3x + 18 Isolate all y interior the left and deliver all x and constants to the staggering. 3y - y = 3x + 18 + 2x + 2 2y = 3x + 2x + 18 + 2 2y = 5x + 20 2y = 5(x + 10) y = (5/2)(x + 10)

2016-10-14 01:33:04 · answer #2 · answered by petrosino 4 · 0 0

y = -2x + 3
2x = 3 - y
x = (3 - y)/2
f(x) = (3-x)/2

it basically involves making x the subject of the equation i.e. x =____ then rewriting it as a function -> f(x).

2007-04-28 16:50:33 · answer #3 · answered by rfedrocks 3 · 0 0

Review your definitions. y IS A FUNCTION OF X exactly the way you have it. We can say y=f(x) to indicate this, where -2x+3 is the f(x).

2007-04-28 16:49:42 · answer #4 · answered by cattbarf 7 · 0 0

x = -0.5y+ 1.5

That should do it.

2007-04-28 16:51:27 · answer #5 · answered by lillimac 2 · 0 0

fedest.com, questions and answers